2016
DOI: 10.9758/cpn.2016.14.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis Artefacta Mimicking Borderline Personality Disorder: Sometimes, Skin Could Be Misleading

Abstract: Dermatitis artefacta lies in a gray zone, between the specialities of psychiatry and dermatology. The condition could mimic a number of other lesions and therefore is a source of much confusion in clinical practice. Here, we describe a case of dermatitis artefacta in an 11-years old girl, which resembled self-harming behavior in Borderline personality disorder. We then discuss how the two could be differentiated and why this becomes imperative while dealing with such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…14 Such scars may be labeled as dermatitis artefacta lesions which come about in "mysterious ways while the patient denies all responsibilities for them". 15 BPD patients first consult dermatology because of these artefactual skin defects. 16 Being able to utilize behavioral therapy is just as important as providing pharmacological therapy for said scars.…”
Section: Dermatological Manifestations Of Personality Disorders In mentioning
confidence: 99%
See 3 more Smart Citations
“…14 Such scars may be labeled as dermatitis artefacta lesions which come about in "mysterious ways while the patient denies all responsibilities for them". 15 BPD patients first consult dermatology because of these artefactual skin defects. 16 Being able to utilize behavioral therapy is just as important as providing pharmacological therapy for said scars.…”
Section: Dermatological Manifestations Of Personality Disorders In mentioning
confidence: 99%
“…given that the incidence of BDD amongst general dermatology patients was found to be 9% to 12% and can be even high as 37% in the cosmetic dermatology setting, whereas the incidence is only 0.7% to 2.4% in the general population. 15 Patients with BDD may "insist on receiving dermatologist treatments such as isotretinoin, dermabrasion, and laser abrasion" even if such treatments are not needed making the patient-physician more difficult. 20 In a study that utilized the BDD questionnaire-dermatology version and objective assessment of acne severity, it was found that amongst patients with mild acne "patients who had used systemic isotretinoin in the past or were currently using this drug were approximately twice as likely to meet criteria for BDD".…”
Section: Body Dysmorphic Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…The typical presentation includes cutaneous lesions, which are bizarre and mimic many of the known inflammatory reactions in the skin. [ 6 , 7 ] The classic location of DA includes the following: face, most common, lower extremity, hands and forearm, trunk, upper arm and shoulder, scalp, and neck. The types of lesions seen in DA are as follows: abrasions or erosions, alopecia, and crusted lesions.…”
Section: Introductionmentioning
confidence: 99%